Parenthood and all-cause mortality in older adults with schizophrenia: a multicenter 5-year prospective study - Katayoun Rezaei; Sandra Abou Kassm; María Sofía Garcés-González; Marina Sánchez-Rico; Mark Olfson; Charles Ouazana-Vedrines; Valentin Scheer; Mahdi Fayad; Pierre Meneton; Frédéric Limosin; Nicolas Hoertel (Brazilian Journal of Psychiatry)
Objective: The large body of literature examining the association between parenthood and mortality in the general population contrasts with a lack of such studies on older adults with schizophrenia. Identifying potential protective factors of premature death in this population is important to help guide prevention measures. Here, we examined whether all-cause and cause-specific mortality rates significantly differ between older parents and non-parents with schizophrenia during a 5-year follow-up. Methods: We used data from a 5-year prospective multicenter sample of older adults with an ICD-10 diagnosis of schizophrenia (aged 55 years or more) recruited in France. We performed a forward stepwise logistic regression to examine the association between parenthood and all-cause mortality, including only independent variables that best explain outcome. Results: Of the 323 older adults with schizophrenia, 133 (41.2%) were parents (mean age = 67.0, SD = 6.1) and 190 were not (mean age = 67.2, SD = 6.6). Following adjustments, parenthood was significantly associated with lower all-cause mortality compared to patients without children (21.1% [n=28] vs. 35.8% [n=68]; AOR = 0.50; 95%CI 0.27-0.94; p = 0.032); the association involved no significant sex differences. Conclusion: Parenthood could be a protective factor against mortality among older patients with schizophrenia who live in France. Further research is needed to understand the specific mechanisms underlying this association.